Achieving ultra-high coefficient of performance of two-phase microchannel heat sink with uniform void fraction. (March 2022) - Jiang, Xingchi; Zhang, Shiwei; Li, Yuanjie; Wang, Zuankai; Pan, Chin
Highlights: Bubble slug ratio maps developed for nearly uniform void fraction distribution. Attain high heat flux of 352.5 W/cm 2 on 12 cm 2 without sign of reaching CHF. Extremely low two-phase flow pressure drop increment with increasing heat flux. Ultra-high coefficient of performance of 75, 675 achieved. Room for significant performance enhancement before reaching CHF. Abstract: Thermal management of high-power electronics/devices has been a very challenging issue for data centers, flourishing electric vehicle revolution as well as cooling of the first wall of a Tokamak fusion reactor. As a prominent cooling strategy, two-phase flow in microchannels has received extensive research over decades. However, inherent defects such as relatively low critical heat flux due to the dry out of liquid film near the exit of the channel and relatively high two-phase flow pressure drop at high heat flux still hinder extensive commercial applications. The present work proposes a robust microchannel heat sink design toward uniform void fraction distribution along the flow direction. The two-phase flow pressure drop will not increase significantly with increase in heat flux. This is made possible by an innovative and unique combination of diverging microchannel and counter-flow manifold, which enables extensive channel-to-channel heat transfer, especially near the end or inlet of the channels. Moreover, flow visualization reveals that nearly uniform void fraction distribution along the channel with relatively high bubble slug ratio is possible. For a relatively large area of 12 cm 2 and under the limitation of wall temperature of 140 °C, a heat flux as high as 3525 kW/m 2 is achieved without sign of reaching the critical heat flux with nearly negligible pressure drop increment comparing to single-phase convection for a relatively low mass flux of 600 kg/m 2 s. An ultra-high coefficient of performance of 75, 675 is attained under a low inlet temperature and low mass flux.